2013
DOI: 10.1182/blood-2012-07-445783
|View full text |Cite
|
Sign up to set email alerts
|

Impaired T-cell responses to sphingosine-1-phosphate in HIV-1 infected lymph nodes

Abstract: Key Points S1P1 activity in human T cells can be reliably measured by assessing downstream signaling events induced upon S1P1 ligation. S1P1 activity is impaired in T cells from HIV-1+ lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…The first rapid phase seen in the first few weeks of therapy is thought to be a consequence of systemic redistribution of sequestered lymphocytes from inflamed and activated lymphoid tissues as viral replication is halted (Bucy et al, 1999) while the second slower phase is thought to represent homeostatic CD4+ T cell restoration. We have recently found that LN T cells in untreated HIV infection have an impaired responsiveness to sphingosine-1 phosphate, the phospholipid that mediates chemotactic egress of lymphocytes from lymphoid tissues (Mudd et al, 2013). This defect can be induced in vitro by both T cell receptor engagement and by exposure to type 1 interferons as well as to a variety of microbial toll-like receptor agonists (Mudd et al, 2013).…”
Section: The Ln In Treated Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first rapid phase seen in the first few weeks of therapy is thought to be a consequence of systemic redistribution of sequestered lymphocytes from inflamed and activated lymphoid tissues as viral replication is halted (Bucy et al, 1999) while the second slower phase is thought to represent homeostatic CD4+ T cell restoration. We have recently found that LN T cells in untreated HIV infection have an impaired responsiveness to sphingosine-1 phosphate, the phospholipid that mediates chemotactic egress of lymphocytes from lymphoid tissues (Mudd et al, 2013). This defect can be induced in vitro by both T cell receptor engagement and by exposure to type 1 interferons as well as to a variety of microbial toll-like receptor agonists (Mudd et al, 2013).…”
Section: The Ln In Treated Hiv Infectionmentioning
confidence: 99%
“…We have recently found that LN T cells in untreated HIV infection have an impaired responsiveness to sphingosine-1 phosphate, the phospholipid that mediates chemotactic egress of lymphocytes from lymphoid tissues (Mudd et al, 2013). This defect can be induced in vitro by both T cell receptor engagement and by exposure to type 1 interferons as well as to a variety of microbial toll-like receptor agonists (Mudd et al, 2013). Treatment with antiretroviral drugs largely (but not completely) corrects this defect thereby providing a mechanistic explanation for the rapid systemic first-phase CD4+ T cell restoration with ART.…”
Section: The Ln In Treated Hiv Infectionmentioning
confidence: 99%
“…7 Patients with IRIS have increased plasma levels of inflammatory cytokines, 8,9 CD4 and CD8 cell activation, 810 increased CD4 cell production of pro-inflammatory cytokines in response to pathogen-derived antigens. 911 Patients with IRIS characteristically have inflammatory infiltrates of affected organs.…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Hart et al[43], constitutive expression of KLF2 in naïve T-cells is extinguished after T-cell stimulation, and cytokines involved in effector differentiation repress re-expression of KLF2. Loss of KLF2 leads, in turn, to transcriptional down-regulation of sphingosine 1-phosphate receptor 1 and thus activated T-cells are retained in lymphoid sites[51]. Furthermore, once CD8+ T-cells are activated, elevated levels of KLF2 are required to maintain the memory cell phenotype[52].…”
Section: Discussionmentioning
confidence: 99%